Defatting of acetone leaf extract of Acacia karroo (Hayne) enhances its hypoglycaemic potential - Idris Njanje; Victor P. Bagla; Brian K. Beseni; Vusi Mbazima; Kgomotso W. Lebogo; Leseilane Mampuru; Matlou P. Mokgotho (BMC, 2017)
Abstract Background Conventional drugs used to treat diabetes are too expensive, toxic and rarely available to rural communities. This study was aimed at investigating the phytochemical differences and hypoglycaemic effects (α-amylase enzyme inhibition, glucose uptake, GLUT4 translocation and phosphorylation of MAPKs) of non-defatted and defatted acetone leaf extract of Acacia karroo. Methods Qualitative phytochemical analyses of extracts were determined using standard chemical tests and total phenolic contents using the Folin-Ciocalteu reagent method. Presence of antioxidant constituents was determined using DPPH scavenging and ferric reducing power assays. Alpha amylase enzyme inhibitory potential was determined chromogenically and cytotoxicity of the extracts on C2C12 muscle and 3T3-L1 cells using the MTT assay. Glucose uptake by the cells was determined colorimetrically and the most active extract was evaluated for its ability to translocate GLUT4 and MAPKs phosphorylation potential using immunofluorescence microscopy and dot blot analysis, respectively. Results Phenols, flavonoids, tannins, saponins and cardiac glycosides were detected in both extracts. Defatting of the plant material resulted in low amounts of phenols (0.432 ± 0.014 TAE/mg), DPPH scavenging activity (EC50 0.40 ± 0.012 mg/ml), low toxicity and high ferric reducing power (EC50 1.13 ± 0.017 mg/ml), α-amylase enzyme inhibition (IC50 30.2 ± 3.037 μg/ml) and glucose uptake by both cells. The defatted extract showed an increase in GLUT4 translocation (at 25 μg/ml) with decrease in Akt expression while in combination with insulin showed a decrease in GLUT4 translocation. A finding, that is implicative that the effect of the extract on GLUT4 translocation in C2C12 cells was not Akt dependent. The defatted extract in the absence and presence of insulin show varying phosphorylation levels of CREB, p38, GSK-3 and ERK2 which are important in cell survival and metabolism. Conclusion This study represents the first report on the hypoglycemic potential of A. karroo and presence of compounds that can be exploited in the search for therapeutics with antidiabetic effect.